The Impacts of a Multifaceted Pre-natal Intervention on Human Capital Accumulation in Early Life - Pedro Carneiro; Lucy Kraftman; Giacomo Mason; Lucie Moore; Imran Rasul; Molly Scott (Institute of Labor Economics (IZA), 2020)
We evaluate an intervention targeting early life nutrition and well-being for households in extreme poverty in Northern Nigeria. The intervention leads to large and sustained improvements in children's anthropometric and health outcomes, including an 8% reduction in stunting four years post-intervention. These impacts are partly driven by information-related channels. However, the certain and substantial flow of cash transfers is also key. They induce positive labor supply responses among women, and enables them to undertake productive investments in livestock. These provide protein rich diets for children, and generate higher household earnings streams long after the cash transfers expire.
Keywords: I15; O15; 330; cash transfers; nutrition